The effects of children's ADHD on parents' relationship dissolution and labor supply - Anette Primdal Kvist; Helena Skyt Nielsen; Marianne Simonsen (Institute for the Study of Labor (IZA), 2011)
This paper uses Danish register-based data for the population of children born in 1990-1997 to investigate the effects on parents of having a child with attention-deficit/hyperactivity-disorder (ADHD). Ten years after birth, parents of children diagnosed with ADHD have a 75% higher probability of having dissolved their relationship and a 7-13% lower labor supply. Exploiting detailed information about documented risk factors behind ADHD, we find that roughly half of this gap is due to selection. However, a statistically and economically significant gap is left, which is likely related to the impact of high psychic costs of coping with a child with ADHD.
urn:nbn:de:101:1-201111213199
Keywords: I12; J12; J13; J22; 330; ADHD; child health; marital dissolution; labor supply; Kinder; Psychische Störung; Eltern; Arbeitsangebot; Scheidung; Schätzung; Dänemark